Effect of HIPEC on Peritoneal Recurrence in Peritoneal Metastasis Treated With Cytoreductive Surgery: A Systematic Review - Yap, Daniel Ren Yi; Wong, Jolene Si Min; Tan, Qiu Xuan; Tan, Joey Wee-Shan; Chia, Claramae Shulyn; Ong, Chin-Ann Johnny (Frontiers in Oncology, 2021)
Background: Peritoneal metastasis (PM) is a late-stage manifestation of intra-abdominal malignancies. The current standard of care indicates that cure can only be achieved with cytoreductive surgery (CRS) which is often indicated with concurrent adjuvant hyperthermic intraperitoneal chemotherapy (HIPEC). However, the utility of HIPEC within subsets of PM is not fully understood. We seek to compare the effectiveness of HIPEC in improving peritoneal recurrence rates in PM of different origins. Methods: We conducted a systematic review of trials on the PubMed, EMBASE, and Cochrane databases, last searched in August 2021. Biases were assessed using the Cochrane Collaboration’s tool for assessing the risk of bias in randomized trials as well as the Methodological Index for Non-Randomized Studies (MINORS) framework. Results: 7, 3, and 3 studies of gastric, ovarian, and colorectal PM respectively were included. Recurrence-free survival was improved in the HIPEC + CRS cohort in 5 gastric trials but only 1 ovarian trial and none of colorectal origin. Discussion: Our findings indicate decent effectiveness of HIPEC in gastric PM, but limited utility in ovarian and colorectal PM. Limitations in the current literature are attributed to the paucity of data available, a lack of homogeneity and consideration of novel and personalised treatment regimens. We implore for further studies to be conducted with a focus on patient selection and stratification, and suggest a reframing of approach towards modern molecular and targeted therapeutic options in future studies of HIPEC.